The Relationship between Nursing Human Resource Management and Nurse Burnout Levels - Partono Siswosuharjo; Al-bahra Al-Bahra; Fathiyati Fathiyati; Abdul Qohar (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2024)
Burnout in nurses is a serious problem that impacts the well-being of nursing staff, service quality, and patient safety. High work demands, limited resources, and weak organizational management make nurses a profession vulnerable to burnout. This study aims to analyze the relationship between nursing human resource (HR) management and nurse burnout levels in hospitals. This study used a quantitative design with a cross-sectional approach. The sample consisted of 120 nurses selected using proportional stratified random sampling. Data were collected through a nursing HR management questionnaire and the Maslach Burnout Inventory (MBI) instrument. Data were analyzed univariately, bivariately using the Chi-Square test, and multivariately using ordinal logistic regression. The results showed that most respondents rated nursing HR management as good, but there were still nurses with moderate to high levels of burnout. Bivariate analysis showed a significant relationship between nursing HR management and nurse burnout levels (p < 0.05). The results of the multivariate analysis revealed that nursing HR management was the dominant factor influencing nurse burnout after controlling for age and length of service. Nurses working in units with poor human resource management are at higher risk of burnout compared to nurses in units with good human resource management. This study concludes that strengthening nursing human resource management plays a significant role in reducing nurse burnout rates. Therefore, human resource management policies and strategies oriented toward nurse well-being are needed to improve the quality of nursing services and patient safety